Pulmonary valve endocarditis in the setting of a patent ductus arteriosus: A rare clinical case - Lamassab Nour El Houda; Noha El Ouafi; Nabila Ismaili (Radiology Case Reports, 2025)
Isolated pulmonary valve (PV) endocarditis is an exceedingly rare entity, accounting for less than 2% of all infective endocarditis cases. Its diagnosis is often delayed due to nonspecific clinical features and the inherent difficulty in visualizing the pulmonary valve on standard transthoracic and transesophageal echocardiography. We report the case of a 43-year-old woman presenting with persistent fever and pulmonary symptoms, in whom transthoracic echocardiography revealed a mobile vegetation on the PV. Despite clear imaging, the diagnosis was initially delayed due to the low index of suspicion and the unusual location of the infection. Further investigation uncovered a silent patent ductus arteriosus (PDA), likely predisposing to endocardial seeding. This case underscores the importance of maintaining clinical vigilance for PV involvement, even in non–IV drug users, and highlights how echocardiography—when carefully interpreted—can reveal rare valvular pathology. Recognition of atypical sites of endocarditis is crucial for timely diagnosis and management.